Konstruksi Dramatik Dalam Lakon Siti Zubaidah: Analisis Struktur Plot Dan Transformasi Naskah - Dhony, Nugroho Notosutanto Arhon; Wadiyo, Wadiyo; Sahid, Nur; Cahyono, Agus (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research discusses the dramatic construction of Dulmuluk Theater, particularly in the play Siti Zubaidah, highlighting its transformation from oral literature to a scripted performance art. This shift indicates efforts toward preservation as well as adaptation to a more structured dramatic form. The scripts used in the performances are sourced from The Syair Abdul Muluk and exhibit a strong coherence, in which each scene supports the other in forming a unified narrative. Through a dramaturgical approach, the analysis of the plot structure is conducted using Gustav Freytag's model, which includes five stages: exposition, complication, climax, resolution, and denouement. The study's findings indicate that Dulmuluk Theater not only possesses a systematic plot construction but also conveys moral and social values through the representation of characters, conflicts, and story resolution. Thus, the Dulmuluk Theatre has the potential to become an educational and reflective medium in the development of traditional performing arts rooted in local wisdom.